2017
DOI: 10.1371/journal.pone.0174924
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric effects of sectional adjustments of collimator angles on volumetric modulated arc therapy for irregularly-shaped targets

Abstract: PurposeTo calculate an optimal collimator angle at each of sectional arcs in a full-arc volumetric modulated arc therapy (VMAT) plan and evaluate dosimetric quality of these VMAT plans comparing full-arc VMAT plans with a fixed collimator angle.MethodsSeventeen patients who had irregularly-shaped target in abdominal, head and neck, and chest cases were selected retrospectively. To calculate an optimal collimator angle at each of sectional arcs in VMAT, integrated MLC apertures which could cover all shapes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In a previous study, we demonstrated the potential of optimal collimator angles during the VMAT delivery for abdomen, head and neck, and chest cases, all of which had an irregularly shaped target, showing high reduction of the total MUs and improvement of dosimetric plan quality, compared to a fixed collimator angle. In that study, Colli-VMAT Pre plans with angular sections of 40° could cover the large and irregularly shaped target, and by using a DICOM-RT format file of the conformal arc plan with a collimator setting of 0°, the optimal collimator angles could be calculated effectively [ 16 ]. However, as mentioned above, MLC positions in the conformal arc plans generated with a collimator setting of 0° could not fully express the target outline.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we demonstrated the potential of optimal collimator angles during the VMAT delivery for abdomen, head and neck, and chest cases, all of which had an irregularly shaped target, showing high reduction of the total MUs and improvement of dosimetric plan quality, compared to a fixed collimator angle. In that study, Colli-VMAT Pre plans with angular sections of 40° could cover the large and irregularly shaped target, and by using a DICOM-RT format file of the conformal arc plan with a collimator setting of 0°, the optimal collimator angles could be calculated effectively [ 16 ]. However, as mentioned above, MLC positions in the conformal arc plans generated with a collimator setting of 0° could not fully express the target outline.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we determined the optimal collimator angles with various angular sections using the conformal arc plans with a fixed collimator angle of 0° and then demonstrated that VMAT plans with the optimal collimator angles with angular sections of 40° and 60° (Colli-VMAT Pre (40°), Colli-VMAT Pre (60°)) reduced the total MUs and improved the sparing of normal organs, compared to Colli-VMAT Pre (90°), Colli-VMAT Pre (120°), and Std-VMAT [ 16 ]. Std-VMAT plan was one full-arc VMAT plans with a fixed collimator angle, having an angular section of 360°.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations